Ageing and cathepsin inhibition affect the shrinkage of fibre fragments of bovine semitendinosus, biceps femoris and psoas major during heating. (February 2021) - Vaskoska, Rozita; Ha, Minh; Ong, Lydia; Kearney, Gavin; White, Jason D.; Gras, Sally; Warner, Robyn D.
Abstract: This study examines the effects of ageing (1, 14 days), cathepsin inhibition (No or Yes) and temperature (25-90 °C) on the shrinkage of fibre fragments from three bovine muscles ( semitendinosus, biceps femoris and psoas major ) during heating. Shrinkage was quantified using light microscopy images. Muscle fibres (except in psoas major ) had greater transverse shrinkage, and less longitudinal shrinkage in aged than in unaged muscles at temperatures ≥60–75 °C . In addition, cathepsin inhibition during heating at ≥65–90 °C caused greater transverse shrinkage in semitendinosus fibres, and reduced longitudinal shrinkage for all muscles. At temperatures ≥75 °C, the longitudinal and transverse shrinkage of the fibres was correlated for all muscles. Ageing of biceps femoris increases volume shrinkage on a fibre level, and hence potentially cooking loss, while cathepsin activity in the semitendinosus reduces volume shrinkage. In conclusion, cathepsin activity and ageing influence the shrinkage that occurs during heating and these factors should be explored further to enable optimisation of thermal meat processing.